In vitro and in vivo evaluation of fast-dissolving tablets containing solid dispersion of lamotrigine - Mohan, Arti; Gundamaraju, Rohit (International Journal of Pharmaceutical Investigation)
Aim: Investigation of in vitro/in vivo behavior of fast-dissolving tablets containing solid dispersions (SDs) of lamotrigine (LM) was the aim and focus of the present research work. Material and Methods: The effect of various hydrophilic polymers on the aqueous solubility of LM was studied. Polyethylene glycol (PEG 6000) was selected as the vehicle and SDs were prepared by melting and solvent evaporation method (SEM). Evaluation of SD for dissolution indicated SVM was more appropriate as seen from an enhancement in drug dissolution. Infrared spectroscopy, differential scanning calorimetry, and powder X-ray diffraction studies indicated a lack of physicochemical interaction between the drug and the carrier. A total of nine formulations were compressed into fast-dissolving tablets using Avicel pH 102 as a directly compressible filler and ac-di-sol, sodium starch glycolate and crospovidone as super disintegrates and evaluated for preand post-compression parameters and in vitro drug release. Results: Mathematical analysis of in vitro data suggested that first order was most suitable mathematical model for describing the optimized formulation. Stability studies indicated that the effect of storage was insignificant at 5% level of confidence. In vivo studies of pure drug, selected formulation and marketed product were carried out in male Wistar rats and pharmacokinetic (PK) parameters were calculated using PK function for Microsoft Excel. The best formulation has shown Tmax of 0.5 h which was highly significant (P < 0.05) when compared with pure drug and marketed formulation. The statistical significance was assessed by one way analysis of variance. Conclusion: Therefore, the SDs prepared by SEM using PEG 6000 as hydrophilic carrier can be successfully used for improvement of dissolution of LM and resulted in faster onset of action as indicated by in vivo studies.
Keywords: Dissolution profile; hydrophilic carrier; solid dispersion; solubility; solvent evaporation method